ESTIMATION OF CARBON STOCK AND BIOMASS OF MANGROVE IN PANGKAL BABU VILLAGE TANJUNG JABUNG BARAT - Ester Restiana Endang Gelis; Septy Heltria; Lauura Hermala Yunita; Rizky Janatul Magwa; Yoppie Wulanda; Farhan Ramdhani; Muhammad Hafidz Ibnu Khaldun (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2026)
Mangrove ecosystems play a critical role as blue carbon sinks, yet quantitative data on carbon stocks in many coastal villages of Jambi Province remain scarce. This study estimated above- and belowground biomass and carbon stocks in the mangrove ecosystem of Pangkal Babu Village, Tungkal Ilir District, Tanjung Jabung Barat Regency, Jambi Province, Indonesia. A non-destructive inventory method was employed across three stations, with a total of eighteen 10 × 10 m sample plots. Tree diameter at breast height (DBH) was measured for all individuals with DBH ≥ 4 cm, and biomass was computed using the generic allometric equation of Komiyama et al. (2005). Six mangrove species were recorded: Sonneratia alba, Avicennia alba, A.marina, Rhizophora apiculata, R. mucronata, and Bruguiera gymnorrhiza, with a total of 246 individual trees. Mean total biomass was 189.29 ± 69.91 Mg/ha and mean carbon stock was 88.96 ± 32.88 Mg C/ha, equivalent to 326.50 ± 120.70 Mg CO₂e/ha. Station 2 exhibited the highest carbon stock (127.88 Mg C/ha), dominated by Avicennia alba with the highest importance value index (IVI = 97.65). These results confirm that the mangrove ecosystem of Pangkal Babu Village serves as a substantial carbon reservoir and should be prioritized for conservation and rehabilitation programs